2021
DOI: 10.1094/pdis-06-20-1296-a
|View full text |Cite
|
Sign up to set email alerts
|

Genome Resources for Seven Fungal Isolates That Cause Dollar Spot Disease in Turfgrass, Including Clarireedia jacksonii and C. monteithiana

Abstract: Fungi in the genus Clarireedia are widespread and destructive pathogens of grasses worldwide, and are best known as the causal agents of dollar spot disease in turfgrass. Here we report genome assemblies of seven Clarireedia isolates, including ex-types of the two most widespread species, C. jacksonii and C. monteithiana. These datasets provide a valuable resource for ongoing studies of the dollar spot pathogens that include population diversity, host/pathogen interactions, marker development and disease contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Next generation sequencing (NGS) allows for rapid sequencing and identification of pathogens through complete genome sequencing [ 90 ]. Next generation sequencing is used for drafting genomes of pathogens or to discover single nucleotide polymorphisms (SNPs) and single nucleotide variants (SNVs) in a sample [ 91 , 92 , 93 , 94 , 95 ]. This information can be used to determine the pathogen race or lineage [ 93 ].…”
Section: Nucleic Acid-based Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Next generation sequencing (NGS) allows for rapid sequencing and identification of pathogens through complete genome sequencing [ 90 ]. Next generation sequencing is used for drafting genomes of pathogens or to discover single nucleotide polymorphisms (SNPs) and single nucleotide variants (SNVs) in a sample [ 91 , 92 , 93 , 94 , 95 ]. This information can be used to determine the pathogen race or lineage [ 93 ].…”
Section: Nucleic Acid-based Techniquesmentioning
confidence: 99%
“…This technology has been utilized in turfgrass for full genome sequencing of Clarireedia spp. the dollar spot causing pathogens [ 95 ]. The development and application of these and other technologies will provide more efficient detection of turfgrass pathogens.…”
Section: Nucleic Acid-based Techniquesmentioning
confidence: 99%
“…The CAPS method was also examined in silico against the Clarireedia spp. sequences from Salgado-Salazar et al study and found that of the sixteen sequences in GenBank, all but one sample of C. jacksonii is expected to produce two bands [11]. That one sample had a point mutation within the restriction digest region.…”
Section: Discussionmentioning
confidence: 95%
“…The last two species, C. jacksonii and C. monteithiana, are found on grasses worldwide, including the US. Reclassification has rejuvenated research into this pathogen [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These determinants were previously characterized in S. sclerotiorum (Xia et al, 2019), the closest fully sequenced and well characterized relative species to Clarireedia. LWC-10 and HRI11 (Green et al, 2016;Crouch et al, 2021), DRR09 and RB-19 (Crouch et al, 2021), H3 and H2 isolates, representative of C. jacksonii, C. monteithiana, and C. aff. paspali were used in this analysis.…”
Section: At the Genomic Levelmentioning
confidence: 99%